(untitled) (EUROPEAN AND ASIAN LAW REVIEW, 2025)
This study aims to analyze civil liability for breach of obligations in payment services amid the digital transformation of the financial sector. The research employs methods of comparative legal analysis, formal legal interpretation of Uzbek legislation, and examination of judicial practice. Particular attention is paid to critical analysis of Art. 795 of the Civil Code of Uzbekistan regulating banks’ liability for improper execution of payment orders. The study reveals significant gaps in legal regulation, including the lack of a clear definition of payment systems, insufficient regulation of payment system operators’ liability, and the mismatch between bank liability norms and modern challenges of the digital economy. The author proposes specific measures for legislative improvement, including: 1) development of comprehensive regulatory framework for payment system participants’ protection; 2) implementation of banking risk control mechanisms; 3) legislative establishment of payment instruments security standards; 4) harmonization of liability provisions with international standards. The key conclusion emphasizes the need to revise Art. 795 of the Civil Code to strengthen banks’ civil liability, introduce client compensation mechanisms, and establish clear criteria for liability in payment services. The research findings can be used for further reform of payment legislation in Uzbekistan.